دراسة وتقييم أداء الموارد البشرية في المنشآت العامة " نموذج شركات الغزل والنسيج في الساحل السوري " - ديوب محمد عباس; برهوم أديب; إسماعيل نوار (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تحتل عملية تقييم أداء الموارد البشرية أهمية كبيرة في المنشآت العامة ويعود سبب ذلك إلى أهمية استخدام واستثمار اليد العاملة ورفع كفاءتها الإنتاجية باستمرار من أجل تحقيق أهداف هذه المنشآت ، وهذا يستدعي توزيع اليد العاملة على الوظائف المختلفة بما يتلاءم مع كفاءتها ورغباتها ومن أجل ذلك لا بد من تقييم أداء العاملين بشكل مستمر. ومن أجل تقييم الأداء لا بد من التعرض إلى مجموعة من المواضيع الأخرى التي ترتبط بصلة وثيقة بعملية التقييم. لذلك قمنا في البداية بدراسة هذه المواضيع حيث تعرضنا للوظائف وأقسامها المختلفة واستقطاب الموارد البشرية اللازمة لشغل هذه الوظائف عن طريق عملية الاختيار والتعيين وتنمية هذه الموارد عن طريق تدريبها لرفع مستوى أدائها باستمرار بالإضافة إلى دراسة الحوافز المؤثرة على هذا الأداء, ثم انتقلنا إلى دراسة عملية التقييم وخطواتها وأهم الأساليب المتبعة فيها والصعوبات التي يمكن أن تعترض تطبيقها محاولين تقديم ما يفيد في تطوير هذه العملية والعمل على الارتقاء بأداء الموارد البشرية بما ينعكس على رفع أداء المنشآت العامة موضوع البحث. Evaluation the performance of people in public organizations has great importance because of the necessity to invest and use the work power of people and to highlight its competence in production in order to achieve the objectives of the establishments. This needs right distribution of workers in the different occupations that fit their competence, aim, and power. For all these, a continuous evaluation of the performance of the worker needed. In order to evaluate the performance, it is necessary to tackle certain topics which are relevant to the evaluating task. In this research, we first studied these topics when we talked about functions and their parts as well as people who fulfill these functions by choosing, appointing and training them to raise their competence and performance in addition to the affecting factors, then we moved to study the evaluation task, its steps, the methods of its application and the difficulties related to its application. We tried to introduce the benefits of developing this task in raising people’s performance to a high degree in order to improve the performance of public organizations under study.